In vivo study of a homeopathic medicine against Rhipicephalus (Boophilus) microplus in dairy cow - Figueiredo, Amanda [UNESP]; Fantatto, Rafaela Regina; Agnolon, Isabela Cabeca; Lopes, Louyse Gabrielli; Oliveira, Patricia Rosa de [UNESP]; Camargo Mathias, Maria Izabel [UNESP]; Alves, Teresa Cristina; Barioni Junior, Waldomiro; Souza Chagas, Ana Carolina de (Soc Brasileira Farmacognosia, 2018)
The tick Rhipicephalus (Boophilus) microplus (Canestrini, 1887) (Acari: Ixodidae) causes large economic losses to cattle breeders and its control is hampered by problems of resistance to the main commercial synthetic acaricides and the risk of residues in animal products. Alternative controls are important for the sustainability of cattle breeding in tropical regions, principally for organic milk production. This study evaluated the efficacy of a homeopathic preparation to control natural tick infestations. The evaluations were conducted with 24 taurine dairy cows during 12 months. The homeopathic medicine (30 CH + Sulfur 30 CH) was administered in a proportion of 1:100 (v/w) in a formulation with sugar, added to 30 kg of mineral salt. This preparation was supplied along with concentrated feed (2 kg/animal/day). The control group received the same feed mixture without the medicine. The groups were kept in separate paddocks. Data were collected on body weight, packed cell volume and number of engorged female ticks on each animal. Temperature, relative humidity and rainfall were recorded. Engorged females were collected from each group for in vitro comparison of reproductive parameters, and semi-engorged ticks for morpho-histological analysis. The mean results of body weight, packed cell volume and tick number were not statistically different between the control and treated groups: 616.5 kg and 618.6 kg; 27.9% and 27.3%; and 12.19 and 13.58 ticks, respectively. In the in vitro analyses, the average weights of the ticks (0.18 and 0.17 g) and eggs (0.07 and 0.06 g), larval hatching rate (70.1 and 76.6%) and reproductive efficiency index (54.3 and 60.6%) of the control and treated groups, respectively, also were not statistically different. Furthermore, no alteration in the ovaries was detected by microscopic analysis. Therefore, the homeopathic medicine was ineffective to control R. (B.) microplus, although the inclusion of agro-ecological practices might enhance its effect of homeopathy in controlling tick infestations. (C) 2018 Sociedade Brasileira de Farmacognosia. Published by Elsevier Editora Ltda.
Keywords: Cattle Tick; Homeopathy; Alternative medicine; Organic production